ID: 226. Issue 1 (November 2015) - Kaifu, Tomonori; Maruhashi, Takumi; Yabe, Rikio; Chung, Soo-hyun; Seno, Akimasa; Fujikado, Noriyuki; Iwakura, Yoichiro
<x xml:space="preserve">Abstract</x> Dendritic cell immunoreceptor (DCIR) is a C-type lectin receptor with a canonical signal motif for initiating inhibitory signals in the cytoplasmic region. In accordance with the structural insights, Dcir−/− mice spontaneously developed autoimmune-like diseases like sialadenitis and swelling and redness of joints. Thus, DCIR is a pivotal regulator for maintaining the homeostasis of the immune system. Furthermore, Dcir−/− mice not only developed ankylosis, characterized by aberrant cartilage and bone formation, but also increased bone volume, accompanied with the higher number of osteoclasts and osteoblasts (OBs). To understand the role of DCIR in bone metabolism, we dissected the molecular mechanism affecting the bone volume in Dcir−/− mice. Flow cytometry analyses revealed that Dcir−/− mice increased IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pjn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives>-positive T cells in peripheral blood and lymph nodes. Dcir−/− dendritic cells had higher potency to shape IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pjn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives>-positive T cells in the co-culture with wild-type T cells. X-ray histomorphometric analysis revealed that both Rag2−/− Dcir−/− and Ifng−/− Dcir−/− negated the increase of bone volume, suggesting that T cell-secreting IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pjn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> be a pathogenic in the increased bone mass. In in vitro OB culture system, we identified IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pjn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> as an osteogenic factor capable of facilitating mineralization of OBs, indicating that IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pjn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> released from T cells acts on OBs. These findings demonstrate that Dcir−/− mice had increased IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pjn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives>-positive T cells, which accelerates mineralization of OBs, leading to the increased bone volume. Collectively, DCIR plays a key role in maintaining bone homeostasis and IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pjn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> functions as an enhancing factor in bone formation.